Account Persuasive Communication @kuliner_laper in Building Culinary Choice Preferences of TikTok Viewers - Alif Rendi; Mustiawan; Gilang Kumari Putra (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah, Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research is based on the phenomenon of utilizing TikTok as a medium to introduce various culinary options to viewers. This study aimed to understand the persuasive communication carried out by the account @kuliner_laper in building TikTok viewers' culinary preferences. This study used a descriptive qualitative approach. Data collection techniques were performed through interviews, observations, and documentation. The Miles and Huberman model was used for data analysis, which consists of data reduction, data presentation, and conclusion drawing. De Fleur and Ball-Rokeach theory of persuasive communication strategies Ball Roceach, which consists of three strategies, serves as the researchers' reference. The research results show that persuasive communication in the psychodynamic strategy is carried out by providing visual displays of culinary items and the selection of persuasive words, while persuasive communication in the sociocultural persuasion strategy is carried out by adopting the momentum of culinary content trends on TikTok. Additionally, the mention of regional names is part of this strategy. Persuasive communication in the meaning construction strategy is carried out by conveying information that builds the audience's knowledge about culinary products